OBSTÁCULOS Y ERRORES EN EL APRENDIZAJE DEL CONCEPTO DE FUNCIÓN EN LOS ESTUDIANTES DE LA UNIVERSIDAD NACIONAL MICAELA BASTIDAS DE APURÍMAC - Ecos Espino, Alejandro Manuel (2015)
Objective:To identify obstacles and errors that manifest students of the National University of Apurimac –Micaela Bastidasregarding the use of different representations of the function concept. Method:Descriptive study with non-experimental design of simple descriptive type. The collection of information was done through a questionnaire composed of 9 open questions, a sample of 99 students from different careers of the University. Results:Students prevail with the conception of function as an equation. There is a better performance when they work with an algebraic expression that can be evaluated; when they are working in other forms of representation show difficulties to carry out coordination and conversions. Conclusion:It was identified the obstacle of epistemological and cognitive type related to the consideration that a function must be written by a single algebraic expression; and didactic obstacle of non-reversibility of the conversion that does not allow them to carry out conversions in the opposite direction. The errors found concern the association of a function with a formula or a regular curve, and the assessmentmade on the basis of this similarity they may have with other type functions.